STRATEGI KEPALA MADRASAH DALAM MENINGKATKAN DAYA TARIK PENERIMAAN PESERTA DIDIK BARU DI MAN KABUPATEN SORONG - Adhim Ada Masta Mayassa; Abdul Azis Khoiri; Mohammad Masykur (Jurnal Manajemen Pendidikan, 2026)
Objective: This study aims to analyze the strategies employed by madrasah principals to increase the appeal of the new student enrollment process at MAN in Sorong Regency. Methods: This study employs a qualitative approach using a case study design. Data were collected through interviews, observations, and documentation from informants including the madrasah principal, vice principal, teachers, administrative staff, and students. Data analysis was conducted through data reduction, data presentation, and drawing conclusions. Results: The results indicate that the madrasah principal’s strategies to enhance the appeal of the new student admission process involve strengthening the work culture, developing flagship programs, improving the quality of educational services, implementing outreach strategies to the community, and conducting continuous evaluation. The increase in the number of new students is influenced by the principal’s ability to mobilize all components of the madrasah and build a positive image of the institution. Supporting factors for these strategies include the principal’s leadership, cooperation among the madrasah community, flagship programs, and community support, while inhibiting factors include limited facilities, the madrasah’s location, competition among educational institutions, and public perception. Novelty: This study contributes through the finding that the appeal of enrolling new students is influenced not only by promotion, but also by the madrasah’s ability to build quality, institutional identity, and community trust.